(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The study is conducted among selected samples of urban and rural tourist centres of Kerala. It is intended to identify which centres are better in terms of reach of positive social benefits in the opinion of the selected sample respondents of four hundred. Out of which one hundred and fifty one belong to urban centres and the remaining two hundred and forty nine to rural. In all out of the six social impacts identified urban tourist centres of Kerala are leading with highest Mean Scores indicating the benefits are more popularly available in urban centres.